H1N1 and influenza viruses: Why pregnant women might be hesitant to be vaccinated - Mirdamadi, Kamelia (College of Family Physicians of Canada, 2011)
Question I have been encouraging pregnant women to receive both the H1N1 and influenza vaccines since I became aware of Health Canada’s guidelines. However, some of the women in my practice have heard conflicting information, often from media sources, and they are hesitant to be vaccinated. What is the evidence behind these guidelines, and should I really be convincing these women to be vaccinated? Answer Pregnant women and growing fetuses are considered a population vulnerable to H1N1 and influenza viruses. Health Canada published a report in late 2010 estimating that this population was at increased risk of hospitalization and severe outcomes of H1N1 infection. Recommendations included pregnant women as a priority group to receive the H1N1 vaccine as well as the influenza vaccine. This information should be explained unambiguously to pregnant women, and they should be made aware of the sensationalism of media reports, which are often based on opinion and not evidence.